The Response of North Sea Ecosystem Functional Groups to Warming and Changes in Fishing - Thorpe, Robert B.; Arroyo, Nina L.; Safi, Georges; Niquil, Nathalie; Preciado, Izaskun; Heath, Michael; Pace, Matthew C.; Lynam, Christopher P. (Frontiers in Marine Science, 2022)
Achieving Good Environmental Status (GES) requires managing ecosystems subject to a variety of pressures such as climate change, eutrophication, and fishing. However, ecosystem models are generally much better at representing top-down impacts from fishing than bottom-up impacts due to warming or changes in nutrient loading. Bottom-up processes often have to be parameterised with little data or worse still taken as a system input rather than being represented explicitly. In this study we use an end-to-end ecosystem model (StrathE2E2) for the North Sea with 18 broad functional groups, five resource pools, and representations of feeding, metabolism, reproduction, active migrations, advection, and mixing. Environmental driving data include temperature, irradiance, hydrodynamics, and nutrient inputs from rivers, atmosphere, and ocean boundaries, so the model is designed to evaluate rigorously top-down and bottom-up impacts and is ideal for looking at possible changes in energy flows and “big picture” ecosystem function. In this study we considered the impacts of warming (2 and 4°C) and various levels of fishing, by demersal and pelagic fleets, on the structure and function of the foodweb. A key aim is to demonstrate whether monitoring of broad ecosystem groups could assist in deciding whether GES was being achieved. We found that warming raised primary productivity and increased the size (total biomass) of the ecosystem. Warming raised metabolic demands on omnivorous zooplankton and reduced their abundance, thus favouring benthivorous and piscivorous demersal fish at the expense of planktivorous pelagic fish but otherwise had modest effects on energy pathways and top predators, whereas changes in fishing patterns could materially alter foodweb function and the relative outcomes for top predators. We suggest that GES should be defined in terms of an unfished state and that abundances of broad groupings and the balance between them can help to assess whether indicator outcomes were consistent with GES. Our findings underwrite the need for an ecosystem approach for the management of human activities supported by relevant monitoring. We also highlight the need to improve our basic understanding of bottom-up processes, improve their representation within models, and ensure that our ecosystem models can capture growth limitation by nitrogen and other elements, and not just food/energy uptake.